2008
DOI: 10.1158/1535-7163.mct-08-0335
|View full text |Cite
|
Sign up to set email alerts
|

Fas-mediated killing of primary prostate cancer cells is increased by mitoxantrone and docetaxel

Abstract: Therapies for prostate cancer based on Fas (CD95) modulation have been under active development at the preclinical stage using immortalized cell lines. To address clinical applicability, the potential of 11 cultures of primary prostate cancer cells to be killed by Fasmediated apoptosis was investigated. In addition, the effect of the chemotherapeutic agents mitoxantrone and docetaxel on this killing was determined. Apoptosis was induced in patient-derived, primary prostate cancer cells using effector cells eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Hence BP utilizes multiple beneficial mechanisms for action in prostatic stromal cells as compared with other SERMs. Alternatively, this also indicates the potential of BP as a chemoprotectant for prostatic cancer since ER-ß, TNF-α, TGFß1 and Fas/FasL mediated actions have been shown to be important in regulation of prostatic carcinoma [49,50]. However this aspect needs further validation.…”
Section: Discussionmentioning
confidence: 96%
“…Hence BP utilizes multiple beneficial mechanisms for action in prostatic stromal cells as compared with other SERMs. Alternatively, this also indicates the potential of BP as a chemoprotectant for prostatic cancer since ER-ß, TNF-α, TGFß1 and Fas/FasL mediated actions have been shown to be important in regulation of prostatic carcinoma [49,50]. However this aspect needs further validation.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously shown that K562-ncFasL cells induce cytolysis in primary human prostate cancer epithelial cells 12. However, when FasL-expressing T cells were substituted with ncFasL-expressing K562 cells in similar killing assays, RM-1 and LNCaP cells failed to undergo any measurable cytotoxicity (Figure 6a).…”
Section: Resultsmentioning
confidence: 79%
“…We have previously shown that treatment of primary prostate cancer cells with mitoxantrone or docetaxel not only increases Fas expression levels on these cells but improves Fas-mediated killing of drug-treated cells by up to 3-fold 12. As basal levels of Fas were low on RM-1 cells compared with murine TRAMP-C1, human LNCaP, and PC-3 cells (Figure 7a), we sought to increase the expression of this receptor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antineoplastic effects result from triggering of tumor cell apoptosis [11,12,13,14,15,16,17], the efficacy of mitoxantrone in multiple sclerosis has been attributed to apoptosis of lymphocytes and dendritic cells [18]. Furthermore, mitoxantrone may induce cell senescence [19].…”
Section: Introductionmentioning
confidence: 99%